International Security and Protection of the Rights of the Child in the African Continent - Zhaylau, Zh.; Abdilda, D. (Farabi Journal of Social Sciences, 2016)
This analysis focuses on typical issues concerning the international legal aspects of ensuring and protecting the rights of the child in armed conflicts. The world community has entered the third Millennium, but unfortunately, it didn’t get rid of the main blemish, which was fighting. International security and the special protection of children’s rights is a set of comprehensive measures which are aimed to prevent children from participation in hostilities, where they often get injured and die, and from the use of them as spies, porters, servants, to transmit messages, and to set mines and mine clearance, to eliminate rape and other sexual abuse. Such children are robbed of their childhood and exposed to terrible dangers and to psychological and physical suffering.